2021
DOI: 10.20452/pamw.15811
|View full text |Cite
|
Sign up to set email alerts
|

T helpers 17 cell responses induced cardiac hypertrophy and remodeling in essential hypertension

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License (CC BY-NC-SA 4.0), allowing third parties to copy and redistribute the material in any medium or format and to remix, transform, and build upon the material, provided the original work is properly cited, distributed under the same license, and used for noncommercial purposes only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…Th17 cell differentiation was enriched in subgroup III, in which BMI was significantly higher than that in the other subgroups, suggesting that Th17 cell differentiation is related with the clinical characteristics of BMI. Moreover, Th17 cell differentiation is involved in many inflammatory cardiovascular diseases and plays a critical role in the pathogenesis of myocardial dysfunction, 21) which is consistent with the clinical characteristics of subgroup III.…”
Section: Discussionsupporting
confidence: 62%
“…Th17 cell differentiation was enriched in subgroup III, in which BMI was significantly higher than that in the other subgroups, suggesting that Th17 cell differentiation is related with the clinical characteristics of BMI. Moreover, Th17 cell differentiation is involved in many inflammatory cardiovascular diseases and plays a critical role in the pathogenesis of myocardial dysfunction, 21) which is consistent with the clinical characteristics of subgroup III.…”
Section: Discussionsupporting
confidence: 62%
“…22 In 187 hypertensive adults and 70 healthy controls, an increased percentage of Th17 was observed in hypertensive patients, particularly in adults with left ventricular (LV) hypertrophy. 24 Th17 is associated with the progression of NAFLD from NAFL to NASH to liver fibrosis. 25 Previous studies have shown that the liver microenvironment increases macrophage infiltration and hepatocyte balloon-like degeneration by changing the features of the liver Th17 cells, and the mechanism is related to the activation of the C-X-C motif chemokine receptor (CXCR)3/C-X-C motif chemokine ligand (CXCL)9/10 axis.…”
Section: Discussionmentioning
confidence: 99%
“…A study involving 77 patients with HF showed an increase in the IL‐17 plasma level, which was negatively correlated with LVEF and fractional shortening 22 . In 187 hypertensive adults and 70 healthy controls, an increased percentage of Th17 was observed in hypertensive patients, particularly in adults with left ventricular (LV) hypertrophy 24 . Th17 is associated with the progression of NAFLD from NAFL to NASH to liver fibrosis 25 .…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in the use of markers and risk scores as well as in testing their clinical applicability in cardiovascular medicine [25][26][27][28][29][30][31][32][33]. Several factors have been found to be associated with LVH assessed by different modalities [7,16]. Studies performed so far have demonstrated that there is a relationship between CTR and LVM measured by echocardiography [5,34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Increased LV mass (LVM) may arise from multiple molecular mechanism, is associated with adverse clinical outcomes and may implicate clinical decision-making [6,7]. CMR imaging is considered the gold standard for assessment of LVM [8].…”
Section: Introductionmentioning
confidence: 99%